Mekanisme erupsi ignimbrit Kaldera Maninjau, Sumatera Barat - Agung Pribadi; Eddy Mulyadi; Indyo Pratomo (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no1.20073Maninjau is a large collapsed caldera that was resulted from a large eruption of silicic pyroclastic material (220-250 km3), and was distributed to more than 75 km away from the source. Field observations have provided a good understanding to the eruptive mechanism of the Maninjau caldera formation, in respect to their stratigraphy, sedimentology and geochronology of the eruptive products. Two formations have been identifi ed, those are: the Maninjau Formation, comprising a sequence of ignimbrite and surge units erupted from the Maninjau Caldera, and the Malalak Formation as a prominent andesitic fall unit likely derived from the Singgalang - Tandikat Volcano that overlies the Maninjau Formation. The variable velocity of the fl ows suggests that the Maninjau eruption initiated by violent. The later phases of the eruption became more violent and associated with caldera collapse.